FORMULATION AND EVALUATION OF THE HERBAL GEL FOR STAPH INFECTION - Sultana, Rukaiya; Maurya, Priyanka; Vishwkarma, DK; Mishr, Dr. Jai Narayan (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2022)
With the advancement in medication there has also been an evolution of new-new diseases, new pathogens which are multiple drug resistant have come into existence. Nature has blessed us with a vast treasure of medicinal plants. The manufactured herbal topical gels of various concentrations (0.2 percent, 0.4 percent, and 0.6 percent) were examined at three different time intervals, namely day-0, 14th day, and 28th day, immediately after preparation. The above-mentioned parameters were assessed in all of the gels of various concentrations. Physical measurements revealed that perhaps the formulations were light Yellow in colour, with no odour and a sour taste. The consistency and greasiness results were good and non-greasy, while homogeneity, extrudability, and spreadibility were also good.